Hyperthermia with photon radiotherapy is thermoradiobiologically analogous to neutrons for tumors without enhanced normal tissue toxicity. (1st January 2019) - Datta, Niloy Ranjan; Bodis, Stephan
Abstract: The depth dose profiles of photons mirror those of fast neutrons. However, in contrast to the high linear energy transfer (LET) characteristics of neutrons; photons exhibit low LET features. Hyperthermia (HT) inhibits the repair of radiation-induced DNA damage and is cytotoxic to the radioresistant hypoxic tumor cells. Thus, thermoradiobiologically, HT simulates high LET radiation with photons. At temperatures of 39–45 °C, the physiological vasodilation allows rapid heat dissipation from normal tissues. On the contrary, the chaotic and relatively rigid tumor vasculature results in heat retention leading to higher intratumoural temperatures. Consequently, the high LET attributes of HT with photon radiations are mostly limited to the confines of the heated tumor while the normothermic normal tissues would be irradiated with low LET photons. HT thereby augments photon therapy by conferring therapeutic advantages of high LET radiations to the tumors akin to neutrons, while the 'heat-sink' effect spares the normal tissues from thermal radiosensitization. Thus, photon thermoradiotherapy imparts radiobiological advantages selectively to tumors analogous to neutrons without exaggerating normal tissue morbidities. The later has been the major concern with clinical fast neutron beam therapy. Outcomes reported from several clinical trials in diverse tumor sites add testimony to the enhanced therapeutic efficacy of photon thermoradiotherapy.